2000
DOI: 10.1210/endo.141.8.7596
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic Induction of Spermatogenesis in the Hypogonadal Mouse*

Abstract: Abnormal sperm production and reduced fertility have been reported in transgenic male mice lacking the alpha-subtype of the estrogen receptor (ER)alpha or aromatase. The aim of this study was to investigate the role of estrogen in male reproductive function, by determining the effect of estradiol on testicular function in hypogonadal (hpg) mice congenitally lacking gonadotropin; and thus, sex steroid production. hpg mice were treated, at 2-3 months of age, with slow-release estradiol implants, which achieved c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(47 citation statements)
references
References 43 publications
8
39
0
Order By: Relevance
“…adult male rats that received increasing doses of estradiol showed significant decreases in circulating concentrations of FSH and LH, which lead to subsequent reductions in serum and testicular testosterone levels [57]. Surprisingly, the authors of this study also noted a stimulatory effect of low doses of estradiol on FSH, as was demonstrated by studies in the neonate [58], and in adult hypogonadal mice given physiological doses of estradiol [59]. Thus, estrogens can participate in both negative and positive effects on the pituitary in male rodents.…”
Section: Discussionsupporting
confidence: 48%
“…adult male rats that received increasing doses of estradiol showed significant decreases in circulating concentrations of FSH and LH, which lead to subsequent reductions in serum and testicular testosterone levels [57]. Surprisingly, the authors of this study also noted a stimulatory effect of low doses of estradiol on FSH, as was demonstrated by studies in the neonate [58], and in adult hypogonadal mice given physiological doses of estradiol [59]. Thus, estrogens can participate in both negative and positive effects on the pituitary in male rodents.…”
Section: Discussionsupporting
confidence: 48%
“…However, this is paradoxical since estradiol inhibits FSH secretion in GnRH intact animals [Ebling et al 2000;Finkelstein et al 1991;Pitteloud et al 2008] suggesting that the stimulatory effect of estrogen on FSH secretion is unique to animals lacking GnRH signaling. While it is possible serum FSH concentrations were increased in our animals, we believe this to be unlikely because our animals had functional GnRH signaling and the dynamics of FSH synthesis and secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The osmotic minipumps can deliver a constant dose of E2 with a plasma profile similar to that of a slow release pellet, which is commonly used in long-term in vivo studies (Fara & Urquhart 1984, Ebling et al 2000. The major advantage of using osmotic minipumps is that they can be connected to a brain infusion cannula, enabling continuous long term i.c.v.…”
Section: Discussionmentioning
confidence: 99%